1976
DOI: 10.2134/jeq1976.00472425000500030003x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dissolved Oxygen on Redox Potential and Nitrate Removal in Flooded Swamp and Marsh Soils

Abstract: The O2 depletion rates, NO3− loss, and the effects of added O2 on NO3− disappearance and redox potential in four flooded or intermittently flooded soils from the swamp and coastal marshes of Louisiana were quantitatively characterized in a laboratory study. The NO3− added either to the shallow floodwater or mixed with the soil in a suspension rapidly disappeared. Eighty to ninety parts per million NO3− was lost from the soil suspensions in 1 to 4 days and from the floodwater over a soil in 10 to 20 days. No NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Nitrogen losses through denitrification vary greatly and are highly variable across relatively small areas depending on NO 3 levels, moisture status of the soil, available organic matter, microbial distribution, and temperature (Engler et al, 1976; Robertson and Tiedje, 1987; Saad and Conrad, 1993). Spatial and temporal variability of N 2 O and N 2 emission from field soils and grasslands has been well documented by several investigators (Rolston et al, 1978; Ryden et al, 1978; Robbins et al, 1979; Bremner et al, 1980, 1981; Mosier et al, 1981; Blackmer et al, 1982; Parkin, 1993; Velthof et al, 1996) and greatly complicates quantification of N 2 O and N 2 emissions in the field.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen losses through denitrification vary greatly and are highly variable across relatively small areas depending on NO 3 levels, moisture status of the soil, available organic matter, microbial distribution, and temperature (Engler et al, 1976; Robertson and Tiedje, 1987; Saad and Conrad, 1993). Spatial and temporal variability of N 2 O and N 2 emission from field soils and grasslands has been well documented by several investigators (Rolston et al, 1978; Ryden et al, 1978; Robbins et al, 1979; Bremner et al, 1980, 1981; Mosier et al, 1981; Blackmer et al, 1982; Parkin, 1993; Velthof et al, 1996) and greatly complicates quantification of N 2 O and N 2 emissions in the field.…”
Section: Resultsmentioning
confidence: 99%
“…After oxygen has disappeared from a water-logged soil, the need for electron acceptors for facultative anaerobic and true anaerobic organisms results in the reduction of several oxidized components. However, Engler et al 6 found that nitrate loss does not appear to be inhibited by the presence of a small amount of molecular 02 in flooded soils. If an energy source is available to the micro-organisms, nitrate, the higher oxides of manganese, hydrated ferric oxides and sulfate will be reduced.…”
Section: Nitrate Reductionmentioning
confidence: 98%
“…The absence of molecular oxygen is due to the extremely slow rates of gas exchanges between soil and air when the soil is saturated with water {Ponnameruma 1972L Furthermore, the molecular oxygen penetrating the soil is rapidly utilized by aerobic and facultative anaerobic microorganisms (Engler et al 1976). Only a very thin layer in the soil-water interface remains in an oxidized state.…”
Section: Nutrient Fluxes Durirlg Decoml~itionmentioning
confidence: 99%
“…Studies of the factors controlling the oxygenated layer showed that both microbial respiration and chemical oxidation of iron (II} control its thickness {Hutchinson 1957;Ponnameruma 1972}. The importance of the layer in nutrient cycling is related to (a} its capacity to sorb and retain compounds such as phosphate, silica, manganese, cobalt, nickel, and zinc that are present in the supernatant water or diffused .from the reduced zone below {Engler et al 1976;Ponnameruma 1972}, and (b) its ability to cause nutrient transformations such as nitrification~ which releases nitrate to the water column ( Keeney 1972).…”
Section: Nutrient Fluxes Durirlg Decoml~itionmentioning
confidence: 99%